The Ninth Marcel Grossmann Meeting: on recent developments in theoretical and experimental general relativity, gravitation, and relativistic field theories : proceedings of the MGIX MM meeting held at the University of Rome "La Sapienza", 2-8 July 2000 - Gurzadjan, Vahe G.; Jantzen, Robert T.; Ruffini, Remo (World Scientific, 2002)
In 1975 the Marcel Grossmann Meetings were established by Remo Ruffini and Abdus Salam to provide a forum for discussion of recent advances in gravitation, general relativity, and relativistic field theories. In these meetings, which are held once every three years, every aspect of research is emphasized - mathematical foundations, physical predictions, and numerical and experimental investigations. The major objective of these meetings is to facilitate exchange among scientists, so as to deepen our understanding of the structure of spacetime and to review the status of both the ground-based and the space-based experiments aimed at testing the theory of gravitation. The Marcel Grossmann Meetings have grown under the guidance of an International Organizing Committee and a large International Coordinating Committee. The first two meetings, MG1 and MG2, were held in Trieste (1975, 1979).A most memorable MG3 (1982) was held in Shanghai and represented the first truly international scientific meeting in China after the so-called Cultural Revolution. Three years later MG4 was held in Rome (1985). It was at MG4 that "astroparticle physics" was born. MGIXMM was organized by the International Organizing Committee composed of D. Blair, Y. Choquet-Bruhat, D. Christodoulou, T. Damour, J. Ehlers, F. Everitt, Fang Li Zhi, S. Hawking, Y. Ne'eman, R. Ruffini (chair), H. Sato, R. Sunyaev, and S. Weinberg. Essential to the organization was an International Coordinating Committee of 135 members from scientific institutions of 54 countries. MGIXMM was attended by 997 scientists of 69 nationalities. It took place on 2-8 July 2000 at the University of Rome, Italy. The scientific programs included 60 plenary and review talks, as well as talks in 88 parallel sessions. The three volumes of the proceedings of MGIXMM present a rather authoritative view of relativistic astrophysics, which is becoming one of the priorities in scientific endeavour. The papers appearing in these volumes cover all aspects of gravitation, from mathematical issues to recent observations and experiments. Their intention is to give a complete picture of our current understanding of gravitational theory at the turn of the millennium. The Marcel Grossmann Individual Awards for this meeting were presented to Cecille and Bryce DeWitt, Riccardo Giacconi and Roger Penrose, while the Institutional Award went to the Solvay Institute, accepted on behalf of the Institute by Jacques Solvay and Ilya Prigogine. The acceptance speeches are also included in the proceedings
Includes bibliographical references and index
Keywords: Electronic books; Konferenzschrift